Raising exposure and interactions in French through computer - supported collaborative learning - Gabarre, Cecile; Gabarre, Serge (Universiti Putra Malaysia Press, 2010)
This case study is part of an action research conducted in a Malaysian public university aiming to develop a computer supported collaborative learning (CSCL) interface for learners of French as a foreign language at the bachelor level. A real task-based CSCL assignment was implemented in a blended learning setting with online activities added to the curriculum without reducing face-to-face contact hours. In line with engaged learning and learner-led theories, 24 learners were asked to collaborate to carry out a complex task that challenges their linguistic and communication skills as well as their organisational aptitude. This study focuses on an analysis of the learners’ perceptions of the CSCL assignment. Questionnaires and guided interviews were carried out to assess the learners’ evaluation of the online support, the relevance of CSCL in a foreign language acquisition and the benefits of real task based assignments. The increased exposure and interactions in the target language and culture resulted in learners’ higher motivation, confidence, and participation. The majority of learners enjoyed this assignment and admitted the benefits of being increasingly challenged. The tutorial was very well received. However, some learners also confided having suffered from too much stress due to zealous team leaders. The learners’ comments and suggestions provided precious feedback on how to improve the implementation of CSCL in the future